Pemanfaatan Limbah Cangkang Telur sebagai Pupuk Organik Cair di Kecamatan Rumbai Bukit - Saberina Hasibuan; Muhammad Rafi Nugraha; Aufa Kevin; Novan Rumbata; Syahkila Syahkila; Sekar Asmara Dhewanty; Muhammad Fajar Fadillah; Maya Kurniati; Nana Trilanda; Sherina Nur Afifah; Tevania Shafira (PRIMA: Journal of Community Empowering and Services, 2021)
Utilization of Eggshell Waste As Liquid Organic Fertilizer in Rumbai Bukit District. Eggshell waste can be used for the manufacture of liquid organic fertilizer. Eggshells can come from laying hens farm waste and household kitchen waste. The utilization of liquid organic fertilizer (POC) from eggshell waste is done to minimize environmental pollution. In addition, eggshell waste recycling has economic value. The activity of making liquid organic fertilizer was carried out by 10 Kukerta students, Riau University. The location for making liquid organic fertilizer is in the yard of Mr. Masdi's house, the chairman of RW 7, Rumbai Bukit District. The method of making liquid organic fertilizer is by fermentation for 10 days at a temperature of around 40oC. The materials used are eggshells, EM4 solution, brown sugar, and water, while the tools needed are a basin, a bottle, a grinder, and a thermometer. The purpose of this program is to increase the knowledge of the residents of Rumbai Bukit on the benefits of eggshell waste in making POC. So far, eggshell waste has only been piled up on vacant land belonging to the village and as a source of air pollution. Making POC from 1 kg of eggshell powder produced 500 ml. During the practice, 7 bottles of POC were produced containing 500 mL per bottle with a capital of Rp. 5,000 per bottle. POC testing on chili and papaya plants planted in people's yards was carried out with qualitative observations of the leaves which showed wider leaves than plants that were not given POC. The results of the participation questionnaire to increase the knowledge and skills of the RW 7 Rumbai Bukit community in participating in activities and developing POC manufacturing increased by 87.5%. This outreach activity adds to the value of eggshell waste every 1 kg after it becomes a POC, which is sold for a profit of Rp. 10,000. Utilization of eggshell waste as POC can increase the economy of the Family Welfare Development (PKK) women's group by 50%.